Highly Sensitive Photodetector Based on Transfer-Free 3-D Graphene on SiO2 - Lee, Bom; Nasir, Tuqeer; Cho, Sooheon; Jung, Myeongjin; Kim, Bum Jun; Lee, Sang Hoon; Jang, Han Eol; Kang, Joohoon; Yu, Hak Ki; Choi, Jae Young (IEEE Sensors Journal, 2024)
Graphene has exceptional optoelectronic and photonic capabilities for diverse applications in solar cells, ultrafast lasers, touch screens, and photodetectors. Here, we report a graphene photodetector synthesized directly on silicon oxide/silicon (SiO2/Si) substrates using the metal-organic chemical vapor deposition technique. The as-grown flake-like 3-D graphene has increased surface area with numerous edge defects originating from flake edges. Additionally, the light absorption in the heavily p-doped SiO2/Si substrate generates an additional photovoltage that effectively modulates the conductance of graphene, leading to high responsivity of 114.64 A/W at a drain voltage of 15 V over a large bandwidth from visible to the near-infrared (IR) region with response and recovery time of 7 ms. In particular, the graphene photodetector achieves an external quantum efficiency (EQE) of 21702.23% and detectivity of 1.24×1011 Jones at a drain voltage of 15 V. This transfer-free and scalable method can lead to low-cost and highly efficient photodetectors.
Keywords: 3D graphene; Diverse applications; Drain voltage; Highly sensitive photodetectors; Photosensor; Si substrates; Synthesised; Transfer-free; Wide-band; Wideband photosensor; Graphene; photodetector; transfer-free; wideband photosensor